2021
DOI: 10.1186/s12877-021-02446-w
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of disease severity, cognitive and physical outcomes of dance interventions for persons with Parkinson’s Disease: a systematic review and meta-analysis

Abstract: Background Patients with Parkinson’s Disease (PD) usually experience worsening of both motor and non-motor symptoms. Dancing has been postulated to help patients with Parkinson’s via several mechanisms that lead to improved physical, cognitive and social functions. Methods This systematic review was conducted following Cochrane methodology and reported following the PRISMA guideline. Four databases (up to June 2021) were searched for RCTs comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 47 publications
(92 reference statements)
1
18
0
Order By: Relevance
“…Sixteen systematic analyses (Mandelbaum and Lo, 2014 ; Sharp and Hewitt, 2014 ; Lötzke et al, 2015 ; Shanahan et al, 2015 ; Aguiar et al, 2016 ; Dos Santos Delabary et al, 2018 ; Kalyani et al, 2019 ; Tang et al, 2019 ; Zhang Q. et al, 2019 ; Barnish and Barran, 2020 ; Berti et al, 2020 ; Carapellotti et al, 2020 ; Hidalgo-Agudo et al, 2020 ; Emmanouilidis et al, 2021 ; Ismail et al, 2021 ; Hasan et al, 2022 ), 18 RCTs (Hackney et al, 2007 ; Hackney and Earhart, 2009 , 2010 ; Hashimoto et al, 2015 ; Rios Romenets et al, 2015 ; Hulbert et al, 2017 ; Shanahan et al, 2017 ; Lee et al, 2018 ; Michels et al, 2018 ; Poier et al, 2019 ; Solla et al, 2019 ; Frisaldi et al, 2021 ), and 62 clinical trials investigated the effects of dance on Parkinson's symptoms ( Tables 1 – 4 , Supplementary Tables 1, 2 ). Most studies (11/13 systematic analyses and all RCTs) examined the effects of dance exercise therapy in PD patients using exercise parameters as the primary outcome measure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sixteen systematic analyses (Mandelbaum and Lo, 2014 ; Sharp and Hewitt, 2014 ; Lötzke et al, 2015 ; Shanahan et al, 2015 ; Aguiar et al, 2016 ; Dos Santos Delabary et al, 2018 ; Kalyani et al, 2019 ; Tang et al, 2019 ; Zhang Q. et al, 2019 ; Barnish and Barran, 2020 ; Berti et al, 2020 ; Carapellotti et al, 2020 ; Hidalgo-Agudo et al, 2020 ; Emmanouilidis et al, 2021 ; Ismail et al, 2021 ; Hasan et al, 2022 ), 18 RCTs (Hackney et al, 2007 ; Hackney and Earhart, 2009 , 2010 ; Hashimoto et al, 2015 ; Rios Romenets et al, 2015 ; Hulbert et al, 2017 ; Shanahan et al, 2017 ; Lee et al, 2018 ; Michels et al, 2018 ; Poier et al, 2019 ; Solla et al, 2019 ; Frisaldi et al, 2021 ), and 62 clinical trials investigated the effects of dance on Parkinson's symptoms ( Tables 1 – 4 , Supplementary Tables 1, 2 ). Most studies (11/13 systematic analyses and all RCTs) examined the effects of dance exercise therapy in PD patients using exercise parameters as the primary outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…MDS-UPDRS-3 evaluated motor functions, such as tremor, bradykinesia, postural instability, rigidity, and gait. Six meta-analyses (Sharp and Hewitt, 2014 ; Lötzke et al, 2015 ; Dos Santos Delabary et al, 2018 ; Kalyani et al, 2019 ; Ismail et al, 2021 ; Hasan et al, 2022 ) reported higher MDS-UPDRS-3 scores on PD patients who had DMT compared with the non-dance group. The DMT group obtained significantly better MDS-UPDRS-3 scores compared with the no treatment or other exercise groups (SMD = −10.73, 95%CI = −15.05 to −6.16, p = 0.004), and standard or other physical therapy (MD= −6.91, 95%CI = −9.97 to −3.84, p < 0.05) (Sharp and Hewitt, 2014 ; Ismail et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations